FUNCTIONS OF PARENTS HOMESCHOOLING THEIR CHILDREN: THE CASE OF LITHUANIA - Naidaitė, Edita; Stasiūnaitienė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The origins of homeschooling can be traced back to the ideas of John Holt, an educational theorist and advocate of school reform in the 1970s, who argued that schools created an oppressive emotional environment and that education at schools aimed to make children’s achievements meet the standards required of compliant employees. Homeschooling is understood as an independent way of organising a form of individual learning, when the child is educated in a family and community environment using a variety of learning tools and environments. The number of homeschooled children is growing, and more and more parents are becoming interested in this form of education and in the legal aspects of its regulation. This article analyses the case of Lithuania. The aim of the article is to answer the questions of how homeschooling of children is organised and what functions parents perform in homeschooling. The qualitative research approach was chosen to analyse the experiences of parents homeschooling their children and to identify the functions of parents as educators.